Identity Construction through the Use of Code Switching in Online Advertisements - Ting, Su Hie; Siti Sarah, Hosen (UNIMAS Publisher, 2023)
During the COVID-19 pandemic, when economic activities slowed down due to lockdown and disease preventive measures, some businesses adapted fast and moved their businesses online. According to the Minister of Domestic Trade and Consumer Affairs, online buying-and-selling activities spiked by 28.9% in April 2020 (Ruzki, 2019). Overnight, normal social media platforms became means of advertising products and services. For example, Facebook, YouTube, and Instagram are among the most popular social networks worldwide as of January 2022, as shown in Figure 1 (Statista, 2022). Advertisements draw the customer’s attention to the brand and the message of the advertisement. Successful advertisements are those that succeed in persuading customers to buy a certain product or pay for a certain service.